Neoliberalism, Applied Linguistics and the PNLD - Vanderlei J. Zacchi (Ilha do Desterro)
Based on the book Neoliberalism and Applied Linguistics (Block, Gray & Holborow, 2012a), this paper aims at discussing the relationship between these two concepts. After a general discussion on the subject, the paper will deal with the use of celebrities in English language textbooks as an element of identification and as a means to advance neoliberal values. A second aspect refers to the promotion of social and cultural diversity and pluralism in a way that may be also attending to the market’s interests. These aspects will finally be analysed in the series Links(Santos & Marques, 2009a, 2009b, 2009c), of the National Textbook Program (PNLD) for primary education. Whereas the textbooks use celebrities and present other neoliberal tendencies, they also propose activities that seek to promote citizenship and inclusion, probably in order to fulfil the Ministry of Education's demands through PNLD. This ambiguity may be related to the fact that the PNLD is a state-run program for public education that relies on the commercial editorial market to produce and sell the textbooks.